Basic features of a Reflective Middleware for Intelligent Learning Environment in the Cloud (IECL) - Cordero Zambrano, J. (2015)
In this paper is proposed an architecture of a Reflective Middleware, which aims to manage an Intelligent Environment of Learning based in cloud learning, which is modeled using a Multiagent system. The Middleware is able to monitor the environment consisting of physical and virtual objects, intelligent or not, based on the context. The middleware manages educational services in the cloud to enhance the learning experience of students, either collaboratively or individually.